Implementation Of Social Competence Training Based On Religious Moderation Module In Majene, West Sulawesi - Sahupala, Okky Naomi (Fakultas Psikologi, Universitas Islam Negeri Raden Fatah Palembang, Sumatra Selatan, 2025)
Extremist views on religion and disputes amongst religious groups over support are the main causes of conflicts in Indonesia. These disputes are not founded on tolerance at all and run counter to Pancasila norms. This study aims to instill religious moderation in adolescents through social competence training, with the concept of playing based on religious moderation modules. The research method used an experimental method with a one-group pretest and posttest design model, with 28 subjects aged 17 to 20 years. The data collection tools used are the religious moderation scale and the religious moderation-based social competence training module. The results showed that there were differences in the understanding of religious moderation between before and after being given training. Social competence training through the application of religious moderation modules is effective in helping to instill an understanding of religious moderation, which, in this study, focuses on indicators of religious moderation. The form of training with the concept of play can help individuals more easily understand the concept of religious moderation indicators.